Advertising from a semiotic point of view:: the case of the Algerian press - YAHIAOUI, Zoubir (Journal of Human Sciences, 2023)
This research is part of a semiolinguistic perspective. This study is a reflection on the mode of operation of the advertising image, as it exists in the Algerian press. The research mainly focuses on the enunciative characteristics, the narrative organization, the rhetorical means as well as the denotative and connotative aspect of the advertising image. This work is intended as a reflection on the mode of operation of advertising.